Validation of the Cooperative Learning Scale and Cooperation Global Factor Using Bifactor Structural Equation Modelling - Javier Fernandez-Rio; José A. Cecchini; Kevin Morgan; Antonio Mendez-Gimenez; Rhys Lloyd (Psicología Educativa: Revista de los Psicólogos de la Educación, 2022)

(untitled)
Cooperative learning has been found to be more productive in academic, personal, and social variables than individualistic or competitive settings, but there is a lack of adequate assessment instruments. The goals of the study were two: a) adapt and validate the existing Cooperative Learning Scale Spanish version for English-speaking secondary education contexts and b) obtain a cooperation global factor. A total of 778 secondary education students, within the 11-15 age range, enrolled in five different schools in Wales (year seven = 301, year eight = 276, year nine = 201) participated in the study. The original instrument, designed and validated for Spanish contexts, underwent a process of double debugging: a) experts trial and b) pilot study. The Cooperative Learning Scale English version included five factors with three items each: interpersonal skills, group processing, positive interdependence, promotive interaction, and individual accountability. Novel bifactor exploratory structural equation modelling (B-ESEM) was used. Results showed well-defined factors corresponding to a-priori expectations and a G-factor, a cooperation global factor.